Analysing Corporate Governance Research in the Pharmaceutical Industry: A Bibliometric Study - Sangeetha Narayanan; Subhendu Kumar Pradhan (Qubahan Academic Journal)
This study examines the current body of literature on Corporate Governance, aiming to provide an overview of publication metrics, collaboration patterns, key areas of focus, emerging trends in research, and potential future avenues for an investigation. To achieve the goals of this research, a range of bibliometric methods were employed. These included performance analysis, citation analysis, network analysis, trend analysis, and thematic mapping. These techniques were applied to a dataset of 303 documents sourced from the Scopus database, spanning the years 1987 to 2023.  The Biblioshiny application of the R-studio software was utilized for this purpose. Extensive investigations of Corporate Governance began in 2008. The United States is the leading contributor, followed by the United Kingdom, and the majority of the leading contributors collaborate. The research pinpointed the most prominent journals, authors, and publications within the field by conducting a thorough citation analysis. The study offers a crucial understanding of the current state of research and suggests avenues for future research to fill this research gap.